Detection of Legionella spp. from Domestic Water in the Prefecture of Arta, Greece. (12th March 2014) - Dimitriadi, Dimitra; Velonakis, Emmanuel
Abstract : The aim of this research was the isolation of Legionella spp. from domestic water supply networks in the Prefecture of Arta. A total of 100 water samples, from 25 houses, were collected. Half of the samples concerned the cold water and half the hot water supply. Purpose was to detect colonization of the water networks with Legionella spp. >500 cfu/L by using the method of filtration (ISO 11731). Out of 100 samples, 6 samples from 3 houses were positive for Legionella spp. Legionella pneumophila serogroup 2–14 was isolated in 5 of 6 samples, whereas in the sixth sample Legionella anisa was identified. Only three of the samples had residual chloride over 0.2 mg/L, rate which is necessary for potable water, according to the Greek hygienic practice. Concerning the temperature of hot water, the mean temperature of the negative for Legionella samples was higher compared to the mean temperature of the positive for Legionella samples (49.9°C versus 45.5°C). It is estimated that there is risk of infection through the use of showers. The low concentration of chloride and the temperature, which was found within the limits favorable to developing Legionella spp. (20–45°C), provide fertile ground for proliferation of the bacteria.